The potential of carbon nanomaterials for advancing high-performance membranes - Goh, Kunli (2016)
Carbon nanomaterials (CNMs) are potential materials to be used as diffusion barriers for membrane-based separations. In particular, carbon nanotubes (CNTs) and graphene-based materials, such as graphene oxide (GO) and reduced graphene oxide (rGO) sheets, have displayed exceptional water transport properties and excellent molecular sieving capabilities owing to their unique structures and physicochemical properties. Presently, state-of-the art CNM-based membranes exhibited extraordinary membrane performances but are challenging to fabricate. Mixed-matrix CNM-based membranes, on the other hand, are easier to fabricate. However, it is difficult to fully exploit the remarkable properties when CNMs are encapsulated. Therefore, the emphasis in this work is strategically focused on the fabrication of surface-modified CNM-based membranes in order to strike a balance between the two. The objective is to investigate the potential of CNMs as diffusion barriers with the purpose of advancing membrane performances to alleviate the global water scarcity challenge. This study began with the demonstration of freestanding GO and rGO core barriers in sandwich-architectured poly(lactic acid) (PLA)-graphene composite membranes. Micrometers-thick freestanding GO and rGO barriers exhibited high barrier properties towards oxygen and water vapor molecules. In particular, PLA-rGO showed a significant 87.6% decline in water vapor permeability with a reduction in oxygen permeability by two orders of magnitude. Mechanistic analysis attributed this to the extensive and tortuous diffusion pathway which can be up to 1450 times the thickness of the rGO barrier. To further demonstrate the effectiveness of graphene-based materials, the GO deposition on the surface of a hollow fiber substrate was engineered to only nanometers-thick. At this thickness, the GO deposition was found to serve as an effective selective barrier and achieved 86% higher water permeability without sacrificing on membrane selectivity when used to substitute a part of the hollow fiber selective layer. The relatively lower hydrodynamic resistance of the GO sheets and their two-dimensional structures, which essentially fine-tuned the pore size distribution of the nanofiltration (NF) membrane, constituted the GO sheets as effective selective barriers. Next, functionalized multi-walled carbon nanotubes (MWCNTs) were explored as effective water nanochannels in the hollow fiber selective layer. The water permeability of the membrane was enhanced up to 44% in the NF process with inconsequential impact on the membrane selectivity. Correspondingly, the water flux was increased up to 29% in the active layer-facing-feed water orientation without compromising on the reverse salt flux when using 0.5 M MgCl2 as the draw solution in the forward osmosis process. These empirical findings inspired the amalgamation of both MWCNTs and rGO sheets to give all-carbon nanoarchitectures. The nanoachitectures utilized rGO as effective selective barriers and MWCNTs as water nanochannels to achieve a water permeability of 52.7 L m-2 h-1 bar-1 and an almost 100% rejection rates towards methylene blue, acid orange 7 and rhodamine B solutes. Most importantly, the all-carbon nanoarchitectures demonstrated outstanding membrane stability towards turbulent hydrodynamic flow conditions up to 2000 mL/min cross-flow rate. Physicochemical characterization revealed that the inner graphitic walls of the MWCNTs can serve as anchors for the nanoscale rGO foliates on the outer walls of the MWCNTs to interconnect with the assimilated rGO sheets via van der Waals attractions and pi-pi stacking interactions. In conclusion, this thesis presents a detailed study using graphene-based materials and MWCNTs as selective diffusion barriers on the membrane surfaces for NF and FO processes. The results suggested that the exceptional water transport properties of the CNMs can indeed be translated onto the membrane surfaces to enhance membrane performances under practical membrane hydrodynamic operations. Fundamentally, this work contributes towards the development of surface-modified CNM-based membrane and facilitates the realization of practical, high-performance separations using CNM-based membranes.